Flexible Working Arrangement, Stress, Worklife Balance And Motivation: Evidence From Postgraduate Students As Worker - Maharani, Anita; Intan, Salsabila; Mahlani, Siti Afifah; Berlian, Christian Wahyu (LPPM Universitas Terbuka, 2020)
The purpose of this research is to examine the effect of Flexible Working Arrangement (FWA) and Stress toward Work-Life Balance (WLB). The effect of those two variables, however, is strengthened by motivation. The goal is to provide a better understanding of the Work-Life Balance of Postgraduate students who fulfil multiple roles in their life, managing between academic, work, and family life. The survey used questionnaires for data collection in this research. A quantitative approach uses to analyze the data. The subjects of our sample were postgraduate students at a private university, with a total of 96 respondents. To analyze the data, PLS (Partial Least Square) analysis technique was used through the SmartPLS software. Also, to test the second and third hypotheses, a robustness test was performed to assess between items in the independent, dependent, and moderator variables. Findings. The results indicated that the Flexible Working Arrangement (FWA) is not proven to have a significant effect on the Work-Life Balance of postgraduate students. This research suggests the need to see the role of motivation, and the present of motivation in individual who fulfils multiple roles in life.